Witold Pilecki. Confronting the legend of the “volunteer to Auschwitz” - Ewa Cuber-Strutyńska (Zagłada Żydów)
This article is an attempt to analyse the historical memory of Witold Pilecki functioning in the reference literature and collective consciousness. The author concentrates on their idealising and simplistic elements, which lead to mythologization of Pilecki, and asks about the genesis and purpose of creation of myths about the Captain. Basing on an analysis of the sources, Cuber questions the legitimacy of the two popular expressions used with regard to Pilecki, that is, “volunteer to Auschwitz” and “the author of the first report about the Holocaust.” In this way the author points out the necessity to correct and supplement Pilecki’s biography by means of a careful and cautious analysis of all the available sources.